A new basal lineage and resolution of deep nodes yields an improved backbone phylogeny to study early evolution of Asteraceae - Panero, Jose L. (2014)
A backbone phylogeny that fully resolves all subfamily and deeper nodes of Asteraceae was constructed using 14 chloroplast DNA loci. The recently named genus Famatinanthus was found to be sister to the Mutisioideae?Asteroideae clade that represents more than 99% of Asteraceae and was found to have the two chloroplast inversions present in all Asteraceae except the nine genera of Barnadesioideae. A monotypic subfamily Famatinanthoideae and tribe Famatinantheae are named herein as new. Relationships among the basal lineages of the family were resolved with strong support in the Bayesian analysis as (Barnadesioideae (Famatinanthoideae (Mutisioideae (Stifftioideae (Wunderlichioideae?Asteroideae))))). Ancestral state reconstruction of ten morphological characters at the root node of the Asteraceae showed that the ancestral sunflower would have had a woody habit, alternate leaves, solitary capitulescences, epaleate receptacles, smooth styles, smooth to microechinate pollen surface sculpturing, white to yellow corollas, and insect-mediated pollination. Herbaceous habit, echinate pollen surface, pubescent styles, and cymose capitulescences were reconstructed for backbone nodes of the phylogeny corresponding to clades that evolved shortly after Asteraceae dispersed out of South America. No support was found for discoid capitula, multiseriate involucres or bird pollination as the ancestral character condition for any node. Using this more resolved phylogenetic tree, the recently described Raiguenrayuncura + Mutisiapollis telleriae fossil should be associated to a more derived node than previously suggested when time calibrating phylogenies of Asteraceae.